Plan de negocios para exportación de autopartes a Santiago de Chile, por la empresa Sopartes Isazi (2017)
The present Degree Project exposes the methodology and results of a business plan study to carry out the export of Brake Autoparts to Santiago de Chile by the company Sopartes Isazi. A marketing analysis is carried out, where a review of the company and its product to be exported is made. Then, an analysis of the client, the competition and the size of the market is made, where it shows the pre-feasibility of exporting these products to Santiago de Chile. It identifies the opportunities generated by the commercial agreements between Colombia and Chile for the auto parts sector, which are ACE No. 24, and the Pacific Alliance. In which, the latter, provides a 0% tariff for this type of product. And the logistics part is done through the Incoterm CPT.